Retaining Literature in the Indonesian ELT Curriculum - Hamzah Puadi Ilyas (Universitas Syiah Kuala, 2016)
This article presents serious independent arguments why literature needs to be retained in the Indonesian ELT (English Language Teaching) curriculum. In general, ELT curriculum nowadays seems to neglect the importance of literature since the introduction of the communicative approach. Three aspects are presented in connection with why the notion may need immediate application: (1) literature brings many advantages to Indonesian ELT learners; (2) literature can be used to teach critical thinking skills; and (3) critical thinking can be used to promote tolerance. This article is developed based on mainly the ideas of literature teaching proposed by Collie and Slater (1987), Lazar (1993), and Ghosn (2002). Hence, critical thinking and tolerance are values not getting serious attention in educational processes in this country even though these values have been included in the National educational objectives for Indonesia.